PENGARUH PENGHARGAAN INTRINSIK DAN PENGHARGAAN EKSTRINSIK TERHADAP MOTIVASI KERJA PEGAWAI (Studi pada Balai Besar Wilayah Sungai Pemali Juana Semarang) - Suryandaru Pudyas Moro, 10.05.51.0021; Waruwu, Penunjang (Students Journal of Economic and Management, 2014)
This study aimed to analyze the influence of Award Intrinsic and extrinsic Award to Employee Work Motivation. The population in this study were all employees of the Central River Region Pemali Juana Semarang.Obyek research in this study is the Central River Region Pemali Juana Semarang. Sampling technique using the